ANALISIS KUALITAS LAYANAN JASA PENGIRIMAN BARANG PADA PT. TIKI JALUR NUGRAHA EKAKURIR DI PONTIANAK - Rahman, Juliadi; Aminuyati, Aminuyati; Achmadi, Achmadi (Universitas Tanjungpura, 2023)
This study aims to determine the quality of goods delivery services at PT. Tiki Jalur Nugraha Ekakurir (JNE) is a consumer activity in assessing goods delivery services. The research method used is descriptive with a qualitative form. The data sources of this research are consumers from JNE Jeruju Jaya Agent Branch and the data are the results of observations and interviews with the head of the agent, the results of interviews with consumers who send goods and the results of interviews with consumers who receive goods. The results showed that the quality of the reliability dimension in this study was quite good. The quality of this responsiveness dimension can be said to be quite good, on the assurance dimension it can be said that the empathy dimension has been implemented very well, and on the tangible dimension it can be said that it has been implemented well